Weight optimization of metal T stiffened panel of a transport aircraft wing using CAE tools. (2020) - Shaikh, Amir; Nithin Kumar, K.C.; Avikal, Shwetank; Harshit,; Chavadaki, Subhash
Abstract: Skin stiffened constructions are common in aircraft structural components that are subjected to compressive loads. The skin is so thin that it provides very little resistance to buckling against in-plane compressive loads. The objective of the design optimization is to obtain the minimum structural weight of the stiffened panel. The MSC/NASTRAN is used for design optimization. Von Misses failure criteria, Panel Buckling criteria (Metal) and Eigen value criteria are incorporated in an automatic way by exploiting the secondary response constraint feature of the design optimizer. The optimizer allows calculating the secondary response quantities at any stage of design optimization, using the primary response quantities like stress values and design variables values as input; and the secondary response constraint is used in defining the design constraints. Therefore, this study reveals that 125 mm stinger spacing is the optimum spacing and this configuration provides a reduction in weight by 22.14%